The first gentleman [compact disc, unabridged] - Clinton, Bill, 1946-; Patterson, James, 1947- (Blackstone Publishing, 2025)
The president of the United States is up for reelection. Her husband is on trial for murder. Is the First Gentleman a killer? Two journalists search for the truth about the political spouse.